Basics of Electrical and Electronics Engineering - Navas K A; Suhail T A (Rajath Publishers Ernakulam, 2019)
KTU 2019 Revised Syllabus.This book is prepared as per the revised syllabus (2019) of Basic Electrical and Electronics Engineering course for APJ Abdul Kalam Technological University. It is prepared using the text books and reference books given in the course syllabus and a few other internationally reputed works. Authors have tried to elucidate the topics such a way that even a mediocre student can assimilate them. Many solved problems, questions and answers, exercise and sample question papers will provide thorough understanding of the topics.
Keywords: EEE